Pengaruh E-Service Quality Dan E-Trust Terhadap Kepuasan Konsumen Maxim Di Kota Tasikmalaya - Silvi Nurul Fauziah; Ari Arisman; Suci Putri Lestari (Pusat Riset dan Inovasi Nasional, 2023)
Technological developments have penetrated in all fields, not only in one area but also in all sectors of human life, including transportation. The internet is needed nowadays, including in the daily activities of the community. The purpose of this study was to determine the effect of e-service quality and e-trust on Maxim consumer satisfaction in Tasikmalaya City. This type of research is quantitative research, with a sampling technique that is non-probabilty sampling and accidental sampling, with a total of 100 respondents. The data collection method in this study is a survey method using a questionnaire that is distributed to respondents online via google form. The data analysis technique in this study uses multiple linear regression analysis which is processed using SPSS 25. The results of this study indicate that the e - service quality variable has a positive and significant effect on customer satisfaction, the e -trust variable also has a positive and significant effect on customer satisfaction. Simultaneously, e-service quality and e-trust have a positive and significant effect on Maxim customer satisfaction in Tasikmalaya City.